Molecular cloning, characterization and expression analysis of MHCI and chemokines CXCR3 and CXCR4 gene from freshwater carp, Catla catla. (25th August 2019) - Banerjee, Rajanya; Roy, Sudeshna; Samanta, Mrinal; Das, Surajit
Abstract: The immune system with large number of molecules protects the host against a plethora of continuously evolving microbes. Major histocompatibility complex (MHC) molecules serve as cardinal elements of the adaptive immune system responsible for the activation of the adaptive immunity in the host. The present study reports MHCI molecule in freshwater carp, Catla catla, and its differential expression in immunologically relevant tissues post‐infection with Gram‐negative and Gram‐positive bacteria. The MHCI sequence of C. catla had 502 bp nucleotides encoding putative 146 amino acids. The phylogenetic analysis exhibited its evolutionary conservation within the Cyprinidae family and formed a different clade with the higher vertebrates. Simultaneously, CXCR3 and CXCR4 chemokines were cloned and characterized for their expression in infected tissues. Analysis of immunologically relevant tissues of the infected fish exhibited an increase of MHCI gene expression and the down‐regulation of CXCR3 and CXCR4 chemokines, indicating a tricky interaction between the innate and adaptive immune system. It was found that intestine, skin and spleen played a crucial role in the contribution of the defense activity which instigated the self‐immunity. These immune activities can provide useful information to understand the interaction of self and non‐self‐ immune system in freshwater fish, Catla catla .